No room for 'green imperialism' - Abd Razak, Dzulkifli (2007)
SECOND Finance Minister Tan Sri Nor Mohamed Yakcop was quoted (by Time, July 9) using the words "green imperialism" in reference to countries, which despite taking advantage of China's cheap labour, complained about her greenhouse gas emissions. The choice of words is indicative of the hypocrisy practised by some countries. It reminded us of similar terms such as "ecological imperialism" used to describe the state of the environment as a result of development. It is appropriate to understand why things are the way they are.